2018
DOI: 10.3390/catal8110501
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Pyrolysis of Polyethylene and Polypropylene over Desilicated Beta and Al-MSU-F

Abstract: The catalytic pyrolysis (CP) of different thermoplastics, polyethylene (PE) and polypropylene (PP), over two types of mesoporous catalysts, desilicated Beta (DeBeta) and Al-MSU-F (AMF), was investigated by thermogravimetric analysis (TGA) and pyrolyzer-gas chromatography/mass spectrometry (Py-GC/MS). Catalytic TGA of PE and PP showed lower decomposition temperatures than non-catalytic TGA over both catalysts. Between the two catalysts, DeBeta decreased the decomposition temperatures of waste plastics further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Figure 1e and Fig. S14 (corresponding to Table S5 ) reveal that this new CO 2 -facilitated upcycling process gives a distinctly higher aromatics yield and BTX yield in comparison to previously reported processes for one-pot upcycling of polyolefins [ 16 , 20–22 , 27–29 ], even though the reaction temperature is lower than 300°C.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Figure 1e and Fig. S14 (corresponding to Table S5 ) reveal that this new CO 2 -facilitated upcycling process gives a distinctly higher aromatics yield and BTX yield in comparison to previously reported processes for one-pot upcycling of polyolefins [ 16 , 20–22 , 27–29 ], even though the reaction temperature is lower than 300°C.…”
Section: Resultsmentioning
confidence: 63%
“…(d) Product yields in the presence of H 2 , He and CO 2 at 300°C. (e) Aromatics yield in this work (denoted by red stars) in comparison to the previously reported values (black circles) for one-pot reactions [ 16 , 20–22 , 27–29 ].…”
Section: Resultsmentioning
confidence: 67%
“…These catalysts lead to lower yields of gases and higher yields of aliphatic liquid products. Furthermore, Lee and Park have used commercial Al-MSU-F and desilicated β-zeolite for the catalytic pyrolysis of PE and PP. These authors observed that the properties of the catalysts strongly affect the results obtained, as higher yields of light and aromatic products are attained with the desilicated β-zeolite.…”
Section: Fast Pyrolysismentioning
confidence: 99%
“…The thermal decomposition of waste plastics can be accelerated with the use of appropriate catalysts. Zeolite, alumina, silica alumina, the FCC catalyst, the reforming catalyst and other catalysts are commonly employed in this process [4,[14][15][16][17]. Table 1 summarizes some of the most common catalysts used in polymer cracking reactions.…”
Section: Introductionmentioning
confidence: 99%